Hybrid Photovoltaic Thermal PVT Solar Systems Simulation Via Simulink/MATLAB - Abdullah, Amira Lateef; Misha, Suhaimi; Tamaldin, Noreffendy; Mohd Rosli, Mohd Afzanizam; Sachit, Fadhil Abdulameer (Penerbit Akademia Baru, 2019)
Photovoltaic-thermal PVT solar system is an emerging solar technology that enables simultaneous conversion of solar energy into electricity and heat. The PV performance was reduced as the temperature increased, PVT systems aim to improve the electrical efficiency by the cooling system by reducing the cell temperature. and the absorber collector took in excess heat underneath the PV. The heat was then transferred through working fluids such as water. The harvested heat was used in low-temperature applications, including domestic hot water supply, water preheating and space heating.In this study, thermodynamic modelling of the thermal and electrical performance of a hybrid PVT water collector was conducted as basis for the design of a new absorber (dual oscillating absorber). The hybrid PVT was compared with normal PV technology (without cooling system) through analysis simulation of the model that was based on theoretical data using MATLAB. A test was performed under solar radiation levels of 300-1000 W/m2 and mass flow rate range of 0.01-0.049 kg/s at each solar radiation level. The results showed that the values of cell efficiency increases with decreasing solar radiation and cell temperature. The cell temperature increases with increasing solar radiation and decreases with the increasing mass flow rate. The outlet water temperature increases with rising solar radiation and decreases as mass flow rate rises.In addition, when the mass flow rate increased, thermal efficiency decreased and increased when solar radiation increased. Analysis was based on design parameters and basic energy balance equations.